Desempenho produtivo e econômico de novilhas Nelore suplementadas no período de transição seca-águas - Pesqueira-Silva, Lilian Chambó Rondena; Zervoudakis, Joanis Tilemahos; Da Silva Cabral, Luciano; Hatamoto-Zervoudakis, Luciana Keiko; Da Silva-Marques, Renata Pereira; Koscheck, Jefferson Fabiano Werner [UNESP]; De Oliveira, André Alves [UNESP] (Universidade Estadual de Londrina, 2015)
The objective of this experiment was to evaluate the body weight gain and the economic viability of Nellore heifers reared on pasture grass Marandu during transition dry-waters receiving energetic, proteic and multiple supplements. Twenty Nelore heifers were used, with average initial body weight of 189.75 ± 21.55 kg distributed in four paddocks of 1.6 ha each. The experimental design was completely randomized (four supplements and five replicates) to evaluate the following supplements: energetic supplement (ES) proteic supplement (PS) and multiple supplement (MS), provided that the amount of 1 kg animal day-1, beyond the exclusive supplement with mineral mixture (MM) ad libitum. The economic evaluation was conducted considering the return of invested capital by dividing the profit margin for the total investment involved in the process of supplementation. The average daily gain (ADG) was higher (P<0.10) for the animals receiving PS (0.68 kg animal day-1) and MS (0.66 kg animal day-1) supplements in relation to MM supplement (0.48 kg animal day-1). The results for average daily gain additional supplement to the MM were 0.088; 0.202 and 0.183 kg day for animals receiving the ES, PS and MS supplements, respectively. In economic terms was observed higher return for the PS supplement (4.38%). The use of proteic supplementation and multiple promoted more productive performance of heifers supplemented grazing in the transition dry-waters, however the multiple supplement resulted in greater economic viability.
Performance and economic evaluation of Nellore heifers supplemented on the dry-rainy season transition period
Keywords: Energetic; Grass Marandu; Multiple; Proteic; Supplementation